Potentials of Predators of Weaver Ants Towards Caterpillar in Palm Plantation with The Test Preferences Method - Irham Falahudin; Shafira Septriani (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2023)
The problem that arises in palm oil plantation operation on a huge scale is the appearance of caterpillar pest that attacks palm oil plants. There are several important pests that attack palm oil plants such as caterpillars which are the sort of Setora nitens. The appearance of the past becomes an important concern for the world’s plantation. How to eradicate the pest naturally is the performed effort. This effort can be done by using weaver ant. Weaver has the potential as the natural enemy of palm oil because they can be nesting in arboreal areas. So, this research object will focus on observing the weaver ant (Ocoephylla smaragdina) predator ability by using the forage preference test method toward several types of dominant pests in palm oil plants, especially caterpillars. Preference for choice and no-choice tests. The material used is an oil palm plantation with four species of caterpillar as the main pest on a palm plantation. The tool used in the test box amount to four in which each of the six different types of caterpillars are inserted. This research is conducted on a laboratory scale by using a complete random program experiment (CRP) and was conducted in April 2016 at Biology Laboratory UIN Raden Fatah Palembang. The research results show that the weaver ant (O. smaragdina) can prey on the S. nitens caterpillar the similarity test average is 87,50% by using a nonchoice technique. The choice methods O. smaragdina can be prey 41,67% S. nitens. In the similarity test average choice techniques are different (83,33%).